Program Stunting: Pembentukan KWT (Kelompok Wanita Tani) dan Penanaman Tanaman Obat Keluarga (TOGA) pada Desa Klampitan, Kecamatan Purwoasri, Kabupaten Kediri - Ahmada Rana Rafidhah; Ahmad Khusaini Khoirudin; Tina Oktavia; Faiz Nurfadzilla; Vicky Ilman Navi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Stunting remains a serious challenge in public health development, particularly in rural areas with limited access to nutrition and healthcare. Klampitan Village, Purwoasri Subdistrict, Kediri Regency, is an agricultural area that still faces cases of children at risk of stunting, with a prevalence of 5.8% in February 2025 (Klampitan Village Posyandu Data, 2025). To address this issue, a community service program was implemented through the establishment of a Women Farmers Group (Kelompok Wanita Tani/KWT) and the cultivation of Family Medicinal Plants (Tanaman Obat Keluarga/TOGA) as a strategy to empower rural women in supporting stunting prevention. The program was carried out over five months using a participatory approach based on Asset-Based Community Development (ABCD) through the stages of preparation, implementation, evaluation, and follow-up. A total of 20 housewives participated as KWT members, focusing on managing a vacant village hall land of approximately 40 m² as well as their respective home gardens. The results showed a significant increase in participants' knowledge, with average pre-test scores rising from 56.3% to 85.7% in the post-test (an increase of 29.4 percentage points). Quantitatively, 56 herbal and vegetable plants were successfully cultivated, including ginger, turmeric, lemongrass, aloe vera, chili, eggplant, and tomato. The KWT served as an effective platform for its members to enhance their skills in managing home gardens into productive farms. TOGA utilization was not only for traditional family medicine but also began to be used as an additional raw material in the village's Supplementary Feeding Program (PMT) as an anti-stunting initiative. Furthermore, the program created opportunities for economic development through plans to diversify TOGA products into processed herbal commodities. The program demonstrates that women's empowerment through KWT can play a significant role in household food security and sustainable stunting prevention.